Impact of swimming initiation on the physical fitness and mental health of elderly women - Daniel Vicentini de Oliveira; Lucas Guilherme Muzolon; Mateus Dias Antunes; José Roberto Andrade do Nascimento Júnior (Universidade Estadual de Maringá, 2019)
This quasi-experimental study aimed to analyze the impact of swimming initiation on the physical fitness and mental health of 10 elderly women. It used the Senior Fitness Test, the Rosenberg Self-esteem Scale, the Geriatric Anxiety Inventory, the Perceived Stress Scale, the WHOQOL-BREF and the WHOQOL-OLD. The program involved 12 weeks of swimming initiation lessons, twice a week. There was significant difference between pre- and post-test in 'sit-to-stand' (p = 0.005), 'elbow flexion' (p = 0.007), 'walk 2.44 m and sit' (p = .005), 'walk 6 min.' (p = 0.005), as well as in anxiety (p = 0.005), stress (p = 0.005), self-esteem (p = 0.007) and quality of life (p < 0.05). Swimming was effective in improving the physical fitness and mental health of the elderly women.